Using Q methodology to investigate pre-service EFL teachers’ mindsets about teaching competences - Irie, Kay; Ryan, Stephen; Mercer, Sarah (Studies in Second Language Learning and Teaching, 2018)
This paper reports on a study investigating the mindsets of 51 pre-service teachers at an Austrian university using Q methodology. Despite the recent growth in interest in the concept of mindsets, little research has addressed the mindsets of teachers – most of it focusing on the mindsets of learners – and the research that does investigate teachers tends to focus on beliefs about learning or intelligence. This study offers a new perspective by focusing on teachers’ beliefs about their own teaching competences. A further aim of the study is to expand the methodological repertoire in language education researchers. This study considers the potential of Q methodology, a research approach used widely in social sciences and education, but, as yet, rare in this field. The data indicate that the most common mindset among the pre-service teachers is one based around a strong belief in the learnability of the more technical aspects of teaching, while interpersonal skills tend to be regarded as more of a natural talent fixed within the individual. One practical implication of this finding is that teacher education programmes may need to pay more attention to explicitly developing the interpersonal side of teaching. A further finding was that teacher mindsets are constructed through individuals’ management of various sets of implicit theories and tend not to conform to the established dichotomous model of mindsets.